Parkin promotes degradation of the mitochondrial pro-apoptotic ARTS protein. - Stav Kemeny (Public Library of Science (PLoS), 2012)
Parkinson's disease (PD) is associated with excessive cell death causing selective loss of dopaminergic neurons. Dysfunction of the Ubiquitin Proteasome System (UPS) is associated with the pathophysiology of PD. Mutations in Parkin which impair its E3-ligase activity play a major role in the pathogenesis of inherited PD. ARTS (Sept4_i2) is a mitochondrial protein, which initiates caspase activation upstream of cytochrome c release in the mitochondrial apoptotic pathway. Here we show that Parkin serves as an E3-ubiquitin ligase to restrict the levels of ARTS through UPS-mediated degradation. Though Parkin binds equally to ARTS and Sept4_i1 (H5/PNUTL2), the non-apoptotic splice variant of Sept4, Parkin ubiquitinates and degrades only ARTS. Thus, the effect of Parkin on ARTS is specific and probably related to its pro-apoptotic function. High levels of ARTS are sufficient to promote apoptosis in cultured neuronal cells, and rat brains treated with 6-OHDA reveal high levels of ARTS. However, over-expression of Parkin can protect cells from ARTS-induced apoptosis. Furthermore, Parkin loss-of-function experiments reveal that reduction of Parkin causes increased levels of ARTS and apoptosis. We propose that in brain cells in which the E3-ligase activity of Parkin is compromised, ARTS levels increase and facilitate apoptosis. Thus, ARTS is a novel substrate of Parkin. These observations link Parkin directly to a pro-apoptotic protein and reveal a novel connection between Parkin, apoptosis, and PD.